An optimal policy for deteriorating items with time-proportional deterioration rate and constant and time-dependent linear demand rate - Trailokyanath Singh; Pandit Jagatananda Mishra; Hadibandhu Pattanayak (Journal of Industrial Engineering International, 2017)
In this paper, an economic order quantity (EOQ) inventory model for a deteriorating item is developed with the following characteristics: (i) The demand rate is deterministic and two-staged, i.e., it is constant in first part of the cycle and linear function of time in the second part. (ii) Deterioration rate is time-proportional. (iii) Shortages are not allowed to occur. The optimal cycle time and the optimal order quantity have been derived by minimizing the total average cost. A simple solution procedure is provided to illustrate the proposed model. The article concludes with a numerical example and sensitivity analysis of various parameters as illustrations of the theoretical results.
Keywords: 650; Constant and time-dependent linear demand rate; Deteriorating items; EOQ Time-proportional deterioration rate